Comparison between supine and prone patient setup for lumbosacral spinal stereotactic body radiosurgery with CyberKnife - Li, Jun; Kong, Xianghui; cheng, Cheng; Wang, Gong; Zhuang, Hongqing; Yang, Ruijie (Frontiers in Oncology, 2023)
Objective: To analyze which tracking modality is more suitable for stereotactic body radiosurgery of lumbosacral spinal tumors by comparing prone and supine patient treatment setup. Methods: 18 patients with lumbosacral spinal tumors were selected. CT simulation was performed in the supine position and prone position respectively. The plans in the supine and prone positions were designed using the XST and XSPT modalities, respectively. The DVH parameters including V100%, D95%, Dmean, CI and HI , as well as Dmax, D0.1cc D1cc and D5cc in the cauda equina and bowel were recorded. The spinal tracking correction errors (alignment error) and correlation errors of the synchrony respiratory model in the prone position were recorded during the treatment. The parameters of correction error and DVH parameters for the two positions were analyzed using the paired t-test to compare the difference in positioning accuracy and dose distribution. Results: For patient setup, the correction error of the supine position in interior/posterior was (0.18 ± 0.16) mm and the prone position was (0.31 ± 0.26) mm (P < 0.05). The correction error of the supine position in inferior/superior was (0.27 ± 0.24) mm and the prone position was (0.5 ± 0.4) mm (P < 0.05). The average correlation errors of the synchrony model for left/right, inferior/superior and anterior/posterior in the prone position were (0.21 ± 0.11) mm, (0.41 ± 0.38) mm and (0.68 ± 0.42) mm. For the dose distribution, Compared with prone plans, the average CI in supine plans was increased by 4.5% (P<0.05). Compared to supine plans, average D1cc and D5cc for the cauda equina was significantly decreased by 4.7% and 15.3% in the prone plan (P<0.05). For the bowel, average Dmax, D0.1cc, D1cc and D5cc were reduced by 8.0%, 7.7%, 5.2% and 26.6% in prone plans (P<0.05) compared to supine plans. Conclusion: Compared with the supine setup, the prone setup combined with XSPT modality for the lumbosacral spinal stereotactic body radiosurgery can spare the bowel and cauda equine of the middle and low dose irradiation, and decrease the number of beams and monitor units.